Acceso al crédito y su relación con el índice de morosidad a nivel nacional periodo 2020-2023 - Bardales Tapayuri, Maydels Aylin (2025)
Access to credit is crucial for economic growth, as it allows families to invest in assets, education, and deal with emergencies. However, financial inclusion remains low in Latin America, with only 30% accessing formal financial products. In Peru, 52% of the population still resorts to informal financing. This study analyzed the relationship between access to credit and the delinquency rate in Peru during the period 2020-2023, with a quantitative approach and a non-experimental design that correlates with the study population to the economic data related to the study variables. The results indicated that there is no statistically significant relationship at the national level, suggesting that delinquency does not depend exclusively on access to credit, but on structural and economic factors. At the regional level, on the Coast, no clear pattern was identified between both variables; Lima maintains high credit availability with low delinquency, while Tumbes presents high delinquency with moderate access. In the Sierra, the relationship is heterogeneous, with regions such as Cusco and Ayacucho showing increases in both variables, while in Cajamarca delinquency decreased despite credit fluctuations. In the Selva, Loreto and Ucayali experienced increases in delinquency without a clear relationship with access to credit. It is recommended to strengthen the evaluation of credit risk, monitor the evolution of delinquency and adapt financing strategies according to the economic conditions of each region.